2017
DOI: 10.1111/aji.12719
|View full text |Cite
|
Sign up to set email alerts
|

Live birth rate following oral antibiotic treatment for chronic endometritis in infertile women with repeated implantation failure

Abstract: Chronic endometritis was found in one-third of infertile women with RIF. The oral antibiotic treatment against CE might be a promising therapeutic option for infertile women with RIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
254
3
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(281 citation statements)
references
References 25 publications
15
254
3
9
Order By: Relevance
“…The efficacy of oral antibiotic treatment for fertility was also elucidated. Kitaya et al conducted a prospective study and found that the LBR in the first ET cycle and three cumulative ET cycles in RIF patients cured by antibiotic treatment (32.8%, 38/116 and 38.8%, 45/116, respectively) was significantly higher than in RIF patients without CE (22.1%, 50/226 and 27.9%, 63/226, respectively) . In this study, the authors set RIF patients without CE as the controls, because almost all CE patients were cured by the antibiotic treatment.…”
Section: Treatment For Ce and Its Effect On Reproductive Outcomesmentioning
confidence: 85%
See 3 more Smart Citations
“…The efficacy of oral antibiotic treatment for fertility was also elucidated. Kitaya et al conducted a prospective study and found that the LBR in the first ET cycle and three cumulative ET cycles in RIF patients cured by antibiotic treatment (32.8%, 38/116 and 38.8%, 45/116, respectively) was significantly higher than in RIF patients without CE (22.1%, 50/226 and 27.9%, 63/226, respectively) . In this study, the authors set RIF patients without CE as the controls, because almost all CE patients were cured by the antibiotic treatment.…”
Section: Treatment For Ce and Its Effect On Reproductive Outcomesmentioning
confidence: 85%
“…30 Kitaya et al also reported that 92.3% (108/117) of CE patients with RIF were cured by the same doxycycline regimen. 35 Additional treatment using a combination of ofloxacin (400 mg/day for 14 days) and metronidazole (500 mg/day for 14 days) cured the remaining 8 of 9 patients. Overall, the cure rate was 99.1% (116/117).…”
Section: Treatment For Ce and Its Effect On Reproductive Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Chronic endometritis refers to inflammation of the endometrium and is often caused by gram-negative bacterial strains such as Escherichia coli and Gardnerella vaginalis or by Ureaplasma urealyticum and Mycoplasma species. 11,12 Interestingly, endometritis is also common in the dairy industry, and bovine uterine infections are estimated to cost the United States 650 million dollars annually. A recent study of infertile women with RIF identified chronic endometritis in almost 34% of their study population, although others have reported the prevalence as high as 57% in women with RIF.…”
mentioning
confidence: 99%